Three Species of Crustacea (Decapoda, Caridea) in Lalar Liang Village, West Sumbawa, Indonesia - Rizky Regina Kawirian; Awan Dermawan; Muhammad Yani Mau (Department of Mathematics and Science Education, Faculty of Teacher Training and Education, University of Mataram. Jurnal Pijar MIPA colaborates with Perkumpulan Pendidik IPA Indonesia Wilayah Nusa Tenggara Barat, 2026)
Freshwater shrimps have a wide distribution in Indonesia's aquatic ecosystems, and play an ecological and economic role that has the potential to improve the community's economy. The entry of invasive species into Indonesian waters is a threat to native species. Therefore, an inventory of native species is needed as a consideration for sustainable fisheries management. However, information regarding the presence and status of freshwater shrimp in West Sumbawa has never been reported. Most rivers in West Sumbawa are seasonal, with high discharge during the rainy season and drying up during the dry season. This research is an exploratory descriptive study using shrimp abundance data calculated as the ratio of individual shrimp counts to the total count across all stations. Samples were collected in March 2026 from three stations during high-water discharge using a traditional bamboo trap called a bubu, which the local Sumbawa people call kodong. This study provides baseline data on three species of freshwater shrimp (Decapoda: Caridea) found in Lalar Liang Village, West Sumbawa. The species obtained were two species of the family Palaemonidae, namely Macrobrachium rosenbergii (De Man, 1879) and Macrobrachium latidactylus (Thallwitz, 1891), and one species of the family Atyidae, Caridina typus (H. Milne Edwards, 1837). The species Macrobrachium rosenbergii (De Man, 1879) had the highest relative abundance (46.67%), followed by Caridina typus (H. Milne Edwards, 1837) (37.33%) and the lowest, Macrobrachium latidactylus (Thallwitz, 1891) (16.00%). These three species are full migrants and natives and are classified as least concern (LC). This study adds to the data on the distribution of freshwater Caridea species in Indonesia and can inform policy-making on ecosystem management, habitat protection, and sustainable freshwater shrimp fisheries.